Czynnik czasu w działalności kierowniczej - Jasiński, Zdzisław; Smolbik-Jęczmień, Alicja (Time factor in management, 2006)
The article presents time management issues of executive personnel. A special attention has been paid to the following questions: importance of time in management, identification of so called „timewasters" and ways to fight them as well as elementary methods of time management which can help you to achieve success. The article consists also of research results concerning the use of work time by managers in Poland and abroad.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 25-33